Wireless UAV Rotary Wing Communication with Ground Nodes Using Successive Convex Approximation and Energy Saving Mode - Sivaganesan, D. (IRO Journal on Sustainable Wireless Systems, 2020)
Communication with several ground nodes (GNs) is enabled through wireless communications by means of a rotary-wing unmanned aerial vehicle (UAV). For every GN, the requirements of communication throughput is satisfied while minimizing the communication and propulsion related energy thereby reducing the total energy consumption of the UAV. The total completion time of the mission, the GN time allocation for communication as well as the trajectory of UAV are optimized jointly to formulate the problem of energy minimization. The UAV rotary wing model of power consumption for propulsion power in a closed-form is also derived. The complexity of the problem increases with the involvement of several variables infinitely over time and the non-convex variables, making it challenging to be solved optimally. The hovering location sets are visited by the UAV and at each location, communication is established with the corresponding GNs. This simplified design for fly-hover-communicate is established for tackling the underlying issue. Convex optimization techniques and travelling salesman problem with neighborhood (TSPN) are leveraged for optimization of the trajectory that connects the hovering locations and the duration of hovering by means of the proposed algorithm design. Communication of the UAV during operation is considered as a general scenario. Discretization of the problem to its equivalent is done in the proposed novel path discretization technique by means of optimized variables of finite number. Further, a successive convex approximation (SCA) scheme is applied for obtaining a solution that is locally optimal. A comparison of the proposed design is performed with the benchmark schemes and it is found that they are outperformed based on numerical results.
Keywords: Path discretization; trajectory optimization; energy-efficient communication; energy model; rotary-wing UAV; UAV communication